1996
DOI: 10.1248/cpb.44.980
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Trazodone-like Analgesic Activity of 4-Phenyl-6-aryl-2-(3-(4-arylpiperazin-1-yl)propyl)pyridazin-3-ones.

Abstract: A series of 4,6-diaryl pyridazinones, chemically related to trazodone, ws synthesized and evaluated for analgesic activity. With ED50 values ranging from 8.4 to 46.7 mg kg(-1) i.p. in the phenylbenzoquinone-induced writhing test (PBQ test), most compounds were several times more potent than acetaminophen (ED50 = 231.3 mg kg(-1) i.p.) and noramidopyrine (ED50 = 68.5 mg kg(-1) i.p.). A multiple linear regression analysis demonstrated a correlation between antinociceptive activity and lipophilicity, as well as el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…[54] The carbonylation occurs preferentially at the b position due to the steric hindrance of the silyl group and the product is obtained in 46-98 % yield. [55] Heterofunctionalized amines such as g-and d-aminoethers, amines and silanes, are easily synthesized by one-pot hydroaminomethylation of the corresponding allylic compounds (Scheme 14).…”
Section: Hydroaminomethylationmentioning
confidence: 99%
“…[54] The carbonylation occurs preferentially at the b position due to the steric hindrance of the silyl group and the product is obtained in 46-98 % yield. [55] Heterofunctionalized amines such as g-and d-aminoethers, amines and silanes, are easily synthesized by one-pot hydroaminomethylation of the corresponding allylic compounds (Scheme 14).…”
Section: Hydroaminomethylationmentioning
confidence: 99%
“…We then proceeded to investigate the 3(2H)-pyridazinones and derivatives carrying acetamide and propanamide moieties at position 2 of the pyridazinone ring and found that these compounds also showed good analgesic and antiinflammatory properties [14,15]. Furthermore, many pyridazinone derivatives have been reported to function as novel potent analgesic and anti-inflammatory agents and some have been shown to selectively inhibit COX-2 function [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Another heterocyclic moiety which has this functional group is the pyridazinone ring system. Many authors previously reported that benzoxazolinone, oxazolopyridinone, and pyridazinone derivatives bearing an arylpiperazine moiety at the side chain on the lactam nitrogen of the rings have significant analgesic activity, and stressed the significance of this structural feature [1,5,6] . In addition, some authors claimed that these compounds exhibit better analgesic activity if they have a three carbon chain between the nitrogen of the lactam and the amine component on the side chain [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that a considerable number of 3(2H)-pyridazinone derivatives have analgesic activity [6,[13][14][15][16][17][18] . Among these compounds, one of the 3(2H)-pyridazinone derivatives, 4-ethoxy-2-methyl-5-morpholino-3(2H)-pyridazinone (emorfazone) is a well-known analgesic and antiinflammatory agent ( Figure 1) [13,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation